The Influence of Esqa X Barbie Co-Branding Design on the Increase of Product Purchase Decisions - Nelson, Feby; Wowor, Erika; Sylviani, Elizabeth Devi (representamen, 2025)
Globalization has created a new way of approaching beauty with the new global beauty standards. The market for cosmetics and facial care have also increased globally, creating a large market for the industry players. ESQA is one of local brands in Indonesia that based on the beauty industry. ESQA itself also offer a new feature in their products by using vegan ingredients. However, the emergence of many new brands in beauty industry is certainly a challenge for business players because the products offered are similar. As a result, ESQA decided to carry out a co-branding with Barbie by creating a series of beauty products in Barbie design that are unique and different from other brands. The purpose of this research is to determine the influence of co-branding carried out by ESQA with Barbie towards product purchasing decisions. This research uses quantitative method and survey methos in data collection. Samples are distributed to 100 followers of the Instagram account @esqacosmetics. The data analysis technique uses simple linear regression analysis to find out how much influence the co-branding between ESQA and Barbie has on product purchasing decisions. The result shows the influence of 0.939. Keywords: Co-branding, ESQA, Barbie, Purchase Decisions